Monitoramento de Ambientes Virtuais Distribuídos com suporte a clientes sob projeção única e multiprojeção - Penteado, Maurício Giacomini (Universidade Federal de São Carlos, 2012)
Immersive, interactive, and collaborative distributed applications, due to their real time and multi-platform characteristics, require a monitoring structure of their functionalities during the development period, which is not fully available in the current monitoring systems, which are usually specific of the languages and platforms in which they are made available. Monitoring systems that require synchronism of distributed objects during the processing is a complex task. Especially in distributed systems from multi-projection where timing is critical to its operation. It is often difficult to check the correct execution of the system. It might be useful for developers and users of such systems to have the ability of identifying, for example, if the reason for the system delay is due to the abusive use of a resource or due to programming mistakes; the identification of which object has crashed, compromising the system as a whole. Distributed object systems, also known as SOA (Service Oriented Architecture), generally use middleware of the broker type in their infrastructure and can have a dynamic number of connected clients or servers when running. There are, in the literature, several tools for the monitoring of performance, resources, debugging, and support, among others, of such systems. Nevertheless, the tools available in the literature are limited to programming languages or platforms that are able to process the monitoring agents related to them. In this work, a tool for the monitoring of distributed object systems is proposed, based on communication described in XML documents, which allows language and platform independence in the such systems development. A structure for the design of tools for the monitoring of distributed object systems is proposed, based on communication described in XML documents, which allows language and platform independence in the such systems development. In addition to the structure that is theoretically founded, the conception of a tool is structured in the manner described and proven in monitoring data from a case study.
Keywords: Ambientes virtuais colaborativos; Sistemas distribuídos; Realidade virtual; CORBA - Common Object Request Broker Architecture; Ambientes Virtuais Distribuídos; Aglomerados Gráficos; Plataforma Jamp; RMI; LibGlass; Ferramentas de Monitoramento; Distributed Virtual Environment; VRCluster; Jamp; RMI; LibGlass; Monitoring Tools; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO